A systematic review of the economic evidence for interventions for family carers of stroke patients. (February 2016) - Heslin, Margaret; Forster, Anne; Healey, Andy; Patel, Anita
Objectives: To examine the economic evidence for interventions aimed at family carers of stroke patients. Data sources: Searches (limited to those published in English since 1990) were performed in key databases along with hand searches of relevant papers. Review methods: Papers were restricted to studies including any economic data (broadly defined) for any intervention targeting carers explicitly or explicitly referring to a carer element, beyond involving carers in the care or intervention for patients (i.e. more than just carers being invited to observe an intervention targeted at the patient). Two reviewers independently screened full papers and extracted data using guidance from the National Institute for Health and Care Excellence, and quality assessment using the Newcastle-Ottawa Quality Assessment Scale (cohort studies), the Delphi list (randomised controlled trials) and guidelines on economic quality from the British Medical Journal. Data were reviewed descriptively as meta analyses were inappropriate due to non-comparability of studies. Results: Ten papers were included in the review. These were heterogeneous in their design, intervention and economic analyses making comparison difficult. Only three of the ten papers included economic evaluations. All three reported that the intervention was less costly and had better or equivalent outcomes than the control comparator although two of these were based on the same intervention using the same dataset. Conclusion: There is some limited evidence that interventions for family carers of stroke patients are effective and cost effective. However, due to variation in the types of interventions examined, little can be concluded regarding implications for clinical practice.